Approaches to Teaching Hadith to the Younger Generation in the Digital Era - Abdullah, Mohd Azam; Shamsudin, Roshimah (Unisia, 2025)
The teaching of hadith to the younger generation is essential in fostering an authentic understanding of Islam and strengthening Muslim identity. However, the challenges of the digital era demand more creative, interactive, and contextually relevant approaches that align with contemporary learning styles. This article explores approaches to hadith instruction through the use of information technology, social media, mobile applications, and e-learning platforms. A qualitative method based on document analysis and literature review was employed to identify effective strategies such as multimedia integration, gamification-based learning, and the use of visual narratives in conveying the values of hadith. The study also highlights the crucial role of educators in guiding youth to distinguish authentic hadith from fabricated information circulating in cyberspace. Findings indicate that innovative digital approaches not only enhance students’ interest and comprehension but also strengthen their attachment to the teachings of the Prophet Muhammad (peace be upon him). This article recommends that digital innovations in hadith pedagogy be continuously enhanced and supported by curricula that are relevant to contemporary challenges.